Transitions in Energy Efficiency and Demand The Emergence, Diffusion and Impact of Low-Carbon Innovation - Jenkins, Kirsten E.H (Routledge Studies in Energy Transitions, 2019)
Meeting the goals enshrined in the Paris Agreement and limiting global temperature increases to less than two degrees above pre-industrial levels demands rapid reductions in global carbon dioxide emissions. Reducing energy demand has a central role in achieving this goal, but existing policy initiatives have been largely incremental in terms of the technological and behavioural changes they encourage. Against this background, this book develops a sociotechnical approach to the challenge of reducing energy demand and illustrates this with a number of empirical case studies from the United Kingdom. In doing so, it explores the emergence, diffusion and impact of low energy innovations, including electric vehicles and smart meters. The book has the dual aim of improving the academic understanding of sociotechnical transitions and energy demand and providing practical recommendations for public policy. Combining an impressive range of contributions from key thinkers in the field, this book will be of great interest to energy students, scholars and decision-makers.